The Influence of the Basotho Culture on the use of Corporal Punishment in the Secondary Schools in Lesotho - Retšelisitsoe Mantoa Matheolane; Alfred Henry Makura (Deanship of Scientific Research (DSR), the University of Jordan, 2020)
This qualitative study sought to determine the influence of Basotho culture in the persistent use of corporal punishment, which is a type of harsh punishment used to control children's disobedience, in Lesotho schools. Lesotho legally abolished the use of corporal punishment in schools. Semi-structured interviews were used to collect data from head-teachers and parents while focus group discussions were used with the learners. Data were analyzed using the thematic approach. Results revealed that corporal punishment was considered a norm within the schools and Basotho society. Additionally, the study found that the use of corporal punishment on children at home, even on toddlers reinforced its use at school. Proverbs were used to justify its use on learners. The use of corporal punishment by teachers was considered normal by the students. The study recommends concerted efforts by key stakeholders in enforcing the laws that proscribe corporal punishment in schools, i.e. parents and learners need to be educated about the sanctity of law.